Community Habits in Floating Houses (Lanting) in Utilizing the River as an Shower, Wash, and Toilet (MCK) Facility in the S. Parman Down Area Neighborhood 01 Hamlet XVII Palangka Raya - Feri Wagiono; Syahrial Shaddiq; Junaidy Junaidy; Dodiet Enggar Wibowo; Muhammad Yusri Dzal Yahya (Universitas of Muhammadiyah Makassar, 2022)
This research on the behavior of people doing acts of his household on the lanting (floating house) and the factors surrounding the community in the use of as an Shower, Wash, and Toilet (MCK) River in the area of Neighborhood Association (RT) 01 Citizens Association (RW) XVII Siswondo Parman (S. Parman) Down the city, Palangka Raya. Type of research is qualitative, subject consists of chairman RT 01, public figures, and residents of the floating house in the safety precautions RT 01 RW XVII S. Parman Down the city Palangka Raya. The data collection techniques in this study use interviews, observation, and documentation techniques. Data analysis techniques used are reduction, data presentation then conclusions. The research showed that floating in safety precautions S. Parman Down RT 01 Kahayan River amounted to ± 80 households and community in the Kahayan River doing Shower, Wash, and Toilet (MCK) activity is accustomed to even become a daily culture of society. Therefore, it is necessary for the role of the local government and the health office to conduct an outreach related to the impact that occurred if the river water as a means of Shower, Wash, and Toilet (MCK) in S. Parman Down RT 01 RW XVII Palangka Raya remains in use.Penelitian ini mengenai perilaku masyarakat yang melakukan kegiatan rumah tangganya di atas lanting (rumah terapung) dan faktor-faktor yang ada di sekitar masyarakat dalam pemanfaatan sebagai Mandi, Cuci, dan Kakus (MCK) Sungai di wilayah Rukun Tetangga (RT) 01 RW XVII Siswondo Parman (S. Parman) bawah kota, Palangka Raya. Jenis penelitian adalah kualitatif, subjek terdiri dari ketua RT 01, tokoh masyarakat, dan penghuni rumah terapung di RT 01 RW XVII S. Parman Bawah Kota Palangka Raya. Teknik pengumpulan data dalam penelitian ini menggunakan teknik wawancara, observasi, dan dokumentasi. Teknik analisis data yang digunakan adalah reduksi, penyajian data kemudian penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kegiatan terapung di S. Parman Down RT 01 Sungai Kahayan berjumlah ± 80 KK dan masyarakat di Sungai Kahayan yang melakukan kegiatan Mandi, Cuci, dan WC (MCK) sudah menjadi kebiasaan bahkan menjadi budaya sehari-hari masyarakat. Oleh karena itu, perlu peran pemerintah daerah dan dinas kesehatan untuk melakukan sosialisasi terkait dampak yang terjadi jika air sungai sebagai sarana Mandi, Cuci, dan Kakus (MCK) di S. Parman Down RT 01 RW XVII Palangka Raya tetap digunakan.